2018
DOI: 10.1016/j.thromres.2018.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of anticoagulant proteins and soluble endothelial protein C receptor in thalassemia patients of Chinese origin

Abstract: Background: Thalassemia is characterized by a hypercoagulable state in which the protein C (PC) pathway controls thrombosis. We investigated changes in PC, protein S (PS), antithrombin III (AT III) and soluble endothelial protein C receptor (sEPCR) in thalassemia. Methods: A group of 129 patients with β-thalassemia major (β-TM), β-thalassemia intermedia (β-TI), α-thalassemia intermedia (α-TI) and combined α-/β-thalassemia (α + β-thal) were compared with 32 gender-and age-matched controls. PC, PS, AT III, sEPCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…PT and APTT were prolonged in 5.55% and 37.03% of our patients with BTM. Prolongation of PT and APTT in BTM patients has been attributed to hepatic parenchymal damage by iron overload [ 14 ], chronic activation of the intrinsic coagulation and/or kallikrein systems following intravascular hemolysis and multiple blood transfusions [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…PT and APTT were prolonged in 5.55% and 37.03% of our patients with BTM. Prolongation of PT and APTT in BTM patients has been attributed to hepatic parenchymal damage by iron overload [ 14 ], chronic activation of the intrinsic coagulation and/or kallikrein systems following intravascular hemolysis and multiple blood transfusions [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shirahata (17) stated that liver impairment was not the only cause of the reduction in natural anticoagulant proteins in β-thalassemia patients. There may be another explanation for the significant decrease in proteins and maybe this type of protein binds to phosphatidylserine, or other negatively charged phospholipids, abnormally exist in the external membrane of the thalassemic erythrocytes (18). This study also showed no significant difference for Protein C, protein S, D-dimer and fibrinogen level found between splenectomized and non-splenectomized patients; the same findings were confirmed by Rosnah( 16) in Malaysia, these findings could been many reports of the hypercoagulable state of thalassemia.…”
Section: Discussionmentioning
confidence: 99%
“…1 Coagulation system activation markers, including low levels of proteins C and S, and increased thrombinantithrombin levels, were observed in these patients. 20 Regular transfusions were found to decrease the risk of thrombosis, whereas splenectomy significantly increased such risk. 1 Along with thrombocytosis that frequently occurs after splenectomy, Trinchero et al 21 reported a prothrombotic state in splenectomized patients, characterized by enhanced platelet activation.…”
Section: Discussionmentioning
confidence: 99%